Role of Intellectual Property Rights in International Business With Special Reference to BRIC Countries - Iyer, Vasudev Parameshwaran (Prabandhan: Indian Journal of Management, 2011)
The World Trade Organisation (WTO) marks the beginning of a new era in the world economic history. A unique feature of WTO has been the extension of international trade rules to cover intellectual property rights (IPRs). WTO agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS), negotiated during the Uruguay Round recognizes that IPRs are private rights and has attempted to establish certain minimum standards of protection that each government has to give to the IPR in dealing with other member countries. IPRs are the cornerstone of efficiency and productivity and hence, of the dynamism and national-level competitiveness. Yet, creation of intellectual property and the generation of IPRs have long been the Achilles’ heel for many countries, especially from the emerging markets like Brazil, Russia, India and China (BRIC). This paper aims at studying the role of IPRs in international business with special reference to BRIC countries. Further, it also makes a cross-country comparison of the IPR regimes in the BRIC countries, and takes a critical look at the factors which may play a key role in the sustenance of economic growth in these countries. The study covers the period between 1995 to 2007.